Poverty and deprivation in Europe - Nolan, Brian, 1953-; Whelan, Christopher T. (Oxford : Oxford University Press, 2011)
This text combines a focus on multidimensionality with a comparative approach to survey the role of non-monetary indicators of deprivation. It shows how poverty varies across countries and over time, who is affected, and which groups should be targeted in framing anti-poverty strategies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Poverty -- European Union countries -- Econometric models; Poverty -- European Union countries; Poor -- European Union countries -- Statistics